Increased Th17/Treg Ratio in Poststroke Fatigue. (18th June 2015) - Liu, Xinjing; Kenkare, Komal; Li, Shanshan; Desai, Varsha; Wong, John; Luo, Xun; Wood, Lisa J.; Xu, Yuming; Wang, Qing Mei
Abstract : Fatigue is a major debilitating symptom after stroke. The biological mechanisms underlying poststroke fatigue (PFS) are unknown. We hypothesized that PSF is associated with an alteration in the balance between Th17 and Treg cells. To test this hypothesis we assessed fatigue in 30 stroke survivors using the Fatigue Scale for Motor and Cognitive Functions (FSMC). Peripheral blood was collected for assessment of Th17 and Treg cell populations and measurement of interleukin-10 (IL-10). Participants were dichotomized into severe fatiguen = 14 and low-moderate fatiguen = 16 groups by K -mean cluster analysis of FSMC scores. There were no group differences in age, gender, stroke type, stroke severity, or time since stroke. Stroke survivors in the severe fatigue group reported greater anxietyp = 0.004 and depressionp = 0.001 than in the low-moderate fatigue group. The ratio of Th17 to Treg cells was significantly increased in the severe fatigue group relative to the mild-moderate fatigue groupp = 0.035 . Serum levels of IL-10 negatively correlated withTh17/Treg ratio (r = - 0.408,   p = 0.025 ). Our preliminary findings suggest that an imbalance in the Th17/Treg ratio is associated with the severity of PSF.